Lupus mimickers (2014)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by multisystem organ involvement, heterogeneity of clinical features, and variety in degree of severity. The differential diagnosis is a crucial aspect in SLE as many other autoimmune diseases portray clinical similarities and autoantibody positivity. Lupus mimickers refer to a group of conditions that exhibit both clinical features and laboratory characteristics, including autoantibody profiles that resemble those present in patients with SLE, and prompt a diagnostic challenge in everyday clinical practice. Thus, lupus mimickers may present as a lupus-like condition (i.e., 2 or 3 criteria) or as one meeting the classification criteria for SLE. Herein we review and classify the current literature on lupus mimickers based on diverse etiologies which include infections, malign and benign neoplasms, medications, and vaccine-related reactions. © 2014 Elsevier B.V.